Forest patch characteristics affect reptile occurrence in north‐western Madagascar. (14th February 2021) - Evans, Alexandra M.; Marshal, Jason P.; Alexander, Graham J.
Abstract: Characterising species–landscape associations is relevant for conservation planning and management in response to environmental transformation. The occurrence of reptiles is linked to landscape structure that allows for thermoregulation, shelter and feeding, but the relative importance of these factors is unknown for many tropical and subtropical species. We used community‐level occupancy modelling and remote sensing to investigate the effects of vegetation structure and anthropogenic development on reptile occurrence in a Malagasy dry forest during the dry season (June and July). The occupancy estimates for some species revealed that species occupancy increased for more densely vegetated sites situated closer to the forest edge. The proximity of anthropogenic transformation did not significantly affect the occurrence of species except for Uroplatus guentheri which showed preference for sites away from settlements. Because most species and those most sensitive to habitat transformation were associated with edges of intact forest patches with denser green vegetation, these areas should form the focus of efforts to conserve reptiles in tropical dry forests. We also demonstrate how setting and scale can affect how habitat‐use patterns are interpreted and the importance of local, species‐specific studies.